A NEW RECORD FROM TURKEY: CONSOLİDA SAMİA P.H. DAVİS (RANUNCULACEAE) - E. Minareci; Y. Altan; T. Aktan (Journal of Animal and Plant Sciences, 2011)
Consolida samia P.H.Davis (Ranunculaceae) is one of the “Top 50 Plants” of IUCN Species Survival Commission. C. samia, as a new record for the Flora of Turkey is described and illustrated from West Anatolia in this study. The specimens were collected from a gravel-like substrate with the largest pebbles in the Balikesir border of Manisa. The description of the species has also been expanded, following collection of specific plant materials. In this study, the detailed morphological characteristics and palynological properties were determined and compared with the closely related taxon C. hellespontica (Boiss.) Chater. Also, line drawing, photographs and a distribution map of C. samia species of Turkey were presented. Our studies led us to recommend it as CR B1ab (iii,v)+2ab(iii,v), according to the 2001 IUCN categories.
Keywords: Consolida; flora; Ranunculaceae; Turkey